2022
DOI: 10.3390/metabo12050458
|View full text |Cite
|
Sign up to set email alerts
|

Metabolomics in Bariatric and Metabolic Surgery Research and the Potential of Deep Learning in Bridging the Gap

Abstract: During the past several years, there has been a shift in terminology from bariatric surgery alone to bariatric and metabolic surgery (BMS). More than a change in name, this signifies a paradigm shift that incorporates the metabolic effects of operations performed for weight loss and the amelioration of related medical problems. Metabolomics is a relatively novel concept in the field of bariatrics, with some consistent changes in metabolite concentrations before and after weight loss. However, the abundance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…First, previous metabolomic studies on bariatric surgery were largely cross-sectional, which did not examine the relationship between a change in metabolites and a change in glycemic outcomes. Second, most previous studies employed a targeted approach by focusing on a preselected list of metabolites, resulting in a low coverage of the metabolome [21,22]. Third, to the best of our knowledge, very few previous metabolomic studies on bariatric surgery examined whether alterations in the blood metabolome underlie the differential glycemic outcomes in response to different types of weight-loss intervention.…”
Section: Introductionmentioning
confidence: 99%
“…First, previous metabolomic studies on bariatric surgery were largely cross-sectional, which did not examine the relationship between a change in metabolites and a change in glycemic outcomes. Second, most previous studies employed a targeted approach by focusing on a preselected list of metabolites, resulting in a low coverage of the metabolome [21,22]. Third, to the best of our knowledge, very few previous metabolomic studies on bariatric surgery examined whether alterations in the blood metabolome underlie the differential glycemic outcomes in response to different types of weight-loss intervention.…”
Section: Introductionmentioning
confidence: 99%
“…Another relevant aspect that has only recently been studied in detail is the metabolic effect of bariatric surgery. Moreover, a recent paper suggested that to manage the complexity of metabolomics it could be useful to exploit artificial intelligence [ 6 ]. However, it is clear that any form of bariatric surgery has a significant impact on nutrients absorption but also on other aspects, including changes in food choice, taste, desire and enjoyment [ 7 ].…”
mentioning
confidence: 99%